Prinsip Common But Differentiated Responsibility Dalam Pengelolaan Lingkungan Hidup, Sumber Daya Alam Dan Hutan Tropis - Oktoberina, Sri Rahayu; Moeliono, Tristam P (Faculty of Law, Parahyangan Catholic University, 2016)
AbstractThe common but differentiated responsibility is or will become an important principle of international environmental law, specifically related to the management of tropical rain forest. The issue at hand is how this principle is understood by developing states, which by its geographical position, is entrusted with the responbility to manage tropical rain forest. In this article the author traces the reason justifying the differentiation of (international) responsibilities and attempts to relate this (mis-) understanding of the principle to Indonesia’ s unwillingness or inability to manage its tropical rain forest.